2018
DOI: 10.1016/j.jaip.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

SJS/TEN 2017: Building Multidisciplinary Networks to Drive Science and Translation

Abstract: Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is a life-threatening, immunologically mediated, and usually drug-induced disease with a high burden to individuals, their families, and society with an annual incidence of 1 to 5 per 1,000,000. To effect significant reduction in short- and long-term morbidity and mortality, and advance clinical care and research, coordination of multiple medical, surgical, behavioral, and basic scientific disciplines is required. On March 2, 2017, an investigator-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
132
0
16

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 202 publications
2
132
0
16
Order By: Relevance
“…ophthalmological or pulmonary sequelae, post-traumatic stress disorder), associated healthcare costs and mortality rate. [4][5][6][7][8][9] Few data are available regarding incidence of and mortality from epidermal necrolysis. 4 Experts in SJS/TEN have recently proposed an annual incidence of one to five cases per million individuals.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 4 more Smart Citations
“…ophthalmological or pulmonary sequelae, post-traumatic stress disorder), associated healthcare costs and mortality rate. [4][5][6][7][8][9] Few data are available regarding incidence of and mortality from epidermal necrolysis. 4 Experts in SJS/TEN have recently proposed an annual incidence of one to five cases per million individuals.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…[4][5][6][7][8][9] Few data are available regarding incidence of and mortality from epidermal necrolysis. 4 Experts in SJS/TEN have recently proposed an annual incidence of one to five cases per million individuals. 4 Hospital-based studies and studies from large electronic databases have found an annual incidence of 1-13 cases per million individuals.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 3 more Smart Citations